The U.S. Combat Aircraft Industry, 1909-2000 - Lorell, Mark A. (RAND Corporation, 2023)
Drawing on primary and secondary sources on the aircraft industry, this report provides a brief survey of industry structure, innovation, and competition in the U.S. fixed-wing combat aircraft industry from its earliest days to the present. It supports a much larger research effort examining the future of the structure, innovation, and competition of the U.S. military aircraft industrial base that responds to congressional concerns about that future.